Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

Entry Island School Yearbook - Entry Island School (2008)

Entry Island School Yearbook - Entry Island School (2004)

The Schools of Entry Island - Entry Island Historical Museum (2003)

Entry Island School Yearbook - Entry Island School (2002)

Entry Island School Yearbook - Entry Island School (2001)

Grosse-Ile High School - Grosse-Ile High School (2000)

Island Schools - Goodwin, Amanda (1997)

May News 1977 Entry Island School - Entry Island School (1977)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1968)